Visualizing Kingship in a Time of Change - Mira Xenia Schwerda (Manazir Journal, 2023)
Despite artistic engagement with photography in Iran almost immediately after the invention of the daguerreotype in 1839, the field of Islamic art history has had difficulty accepting the modern period and the medium of photography as part of its discipline. Studies on painted Iranian portraiture have often stopped before the introduction of photography, and only in more recent years has photographic portraiture and its influence on painting been examined. Due to this nascent state of the field, large gaps exist even on more traditional topics, such as the question of royal portraiture. This article presents the first examination of photographic royal portraiture and the visualization of kingship during the Iranian Constitutional Revolution (1905-1911). This topic, in comparison with earlier Iranian painted royal portraiture, has received considerably less attention. Photographic portraiture, together with printed and painted examples, from the reigns of the Qajar rulers Nasir al-Din Shah (r. 1848-1896), Muzaffar al-Din Shah (r. 1896-1907), Muhammad ʿAli Shah (r. 1907-1909), and Ahmad Shah (r. 1909-1925), will be analysed in connection with social and political developments in order to better understand the development of royal image making during a time of political turmoil.